THAI UNIVERSITY STUDENTS’ ATTITUDES TOWARDS ELF IN CLASSROOM CONTEXTS: A MIXED-METHODS STUDY - Sumit Choemue; Retno Muljani (IAIN Syekh Nurjati Cirebon, 2021)
English has long acted as a powerful language in the world since it is spoken by various people from diverse cultural backgrounds and places around the globe. As a number of non-native speakers (NNSs) are rapidly growing, English as a Lingua Franca (ELF) has become more widespread among English users. This study aimed to investigate Thai university students’ attitudes towards ELF. Particularly, attitudes towards learning English, varieties of English, and ELF used as a medium of instruction in the classroom were examined. Employed a mixed-methods research design, the questionnaire and semi-structured interview were used to collect the data. 23 undergraduate students studying at Xavier Learning Community (XLC), Chiang Rai, Thailand, participated in this study. The findings revealed that effective communication with other English speakers was the paramount goal of learning English. Moreover, the students have begun to express positive attitudes towards different varieties of English used in the classroom as they showed their interest in non-native cultures. This study suggested that supportive learning environments where the students could expose to various varieties of English both inside and outside the classroom would raise their awareness of ELF. Also, ELF teachers should adjust their teaching strategies to meet students’ needs in the future.